Pengaruh komposisi CoFe2O4 terhadap sifat magnetik nanokomposit CoFe2O4/PVDF yang disintesis dengan metode sol gel (The effect of CoFe2O4 composition on the magnetic properties of the CoFe2O4 / PVDF nanocomposites synthesized by the sol gel method) - Sovia Yulianti; - Ramli; - Yulkifli; Yenni Darvina (PILLAR OF PHYSICS, 2020)
Cobalt Ferrite (CoFe2O4) is a magnetic material that has high coercivity, magnetic properties, and has electrical resistivity and high saturation magnetization, very suitable for applications in the field of magnetic, magnetic sensors, magnetic sensor constituents, biomedical materials, Magnetic Resonance Imaging (MRI) and hypertamia. The purpose of the survey is to explain the composition of the CoFe2O4 composition on the magnetic properties of the CoFe2O4 / PVDF nanocomposites synthesized by the Sol-Gel Method. There are three research results from vsm test data on hysteresis curves. First, the magnetization saturation data of each variation obtained results of 2.07 memu, 0.97 memu, 2.18 memu, 1.07 memu, and 0.91 memu. Second, the Remanent Magnetization data obtained results are 0.41 memu, 0.28 memu, 0.35 memu, 0.27 memu, and 0.16 memu. Third, the Medan Coercivity data is 208.31 Oe, 293.42 Oe, 163.20 Oe, 335.88 Oe, and 93.86 Oe.